Charge transfer from and to manganese phthalocyanine: bulk materials and interfaces - Rückerl, Florian; Waas, Daniel; Büchner, Bernd; Knupfer, Martin; Zahn, Dietrich R. T.; Haidu, Francisc; Hahn, Torsten; Kortus, Jens (Beilstein Journal of Nanotechnology, 2017)
Manganese phthalocyanine (MnPc) is a member of the family of transition-metal phthalocyanines, which combines interesting electronic behavior in the fields of organic and molecular electronics with local magnetic moments. MnPc is characterized by hybrid states between the Mn 3d orbitals and the π orbitals of the ligand very close to the Fermi level. This causes particular physical properties, different from those of the other phthalocyanines, such as a rather small ionization potential, a small band gap and a large electron affinity. These can be exploited to prepare particular compounds and interfaces with appropriate partners, which are characterized by a charge transfer from or to MnPc. We summarize recent spectroscopic and theoretical results that have been achieved in this regard.
Keywords: charge transfer; electronic properties; manganese phthalocyanine

(untitled) - Gregory, P. (J. Porphyrins Phthalocyanines, 2000)

(untitled) - Singh, T. B.; Sariciftci, N. S. (Annu. Rev. Mater. Res., 2006)

(untitled) - Rand, B. P.; Genoe, J.; Heremans, P.; Poortmans, J. (Prog. Photovoltaics, 2007)

(untitled) - Li, Y.; Chen, S.; Liu, Q.; Wang, L.; Someya, T.; Ma, J.; Wang, X.; Hu, Z. (J. Phys. Chem. C, 2012)

(untitled) - Lin, Y.; Li, Y.; Zhan, X. (Chem. Soc. Rev., 2012)

(untitled) - Baeg, K.-J.; Binda, M.; Natali, D.; Caironi, M.; Noh, Y.-Y. (Adv. Mater., 2013)

(untitled) - Melville, O. A.; Lessard, B. H.; Bender, T. P. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Gsänger, M.; Bialas, D.; Huang, L.; Stolte, M.; Würthner, F. (Adv. Mater., 2016)

(untitled) - van den Brink, J.; Morpurgo, A. F. (Nature, 2007)

(untitled) - Lach, S.; Altenhof, A.; Tarafder, K.; Schmitt, F.; Ali, M. E.; Vogel, M.; Sauther, J.; Oppeneer, P. M.; Ziegler, C. (Adv. Funct. Mater., 2012)

(untitled) - Djeghloul, F.; Ibrahim, F.; Cantoni, M.; Bowen, M.; Joly, L.; Boukari, S.; Ohresser, P.; Bertran, F.; Le Fèvre, P.; Thakur, P.; Scheurer, F.; Miyamachi, T.; et al. (Sci. Rep., 2013)

(untitled) - Barraud, C.; Bouzehouane, K.; Deranlot, C.; Kim, D. J.; Rakshit, R.; Shi, S.; Arabski, J.; Bowen, M.; Beaurepaire, E.; Boukari, S.; Petroff, F.; Seneor, P.; et al. (Dalton Trans., 2016)

(untitled) - Barraclough, C. G.; Martin, R. L.; Mitra, S.; Sherwood, R. C. (J. Chem. Phys., 1970)

(untitled) - Mitra, S.; Gregson, A.; Hatfield, W. E.; Weller, R. R. (Inorg. Chem., 1983)

(untitled) - Heutz, S.; Mitra, C.; Wu, W.; Fisher, A.; Kerridge, A.; Stoneham, M.; Harker, A.; Gardener, J.; Tseng, H.-H.; Jones, T.; Renner, C.; Aeppli, G. (Adv. Mater., 2007)

(untitled) - Taguchi, Y.; Miyake, T.; Margadonna, S.; Kato, K.; Prassides, K.; Iwasa, Y. (J. Am. Chem. Soc., 2006)

(untitled) - Mazur, U.; Hipps, K. (J. Phys. Chem. B, 1999)

(untitled) - Haidu, F.; Fechner, A.; Salvan, G.; Gordan, O. D.; Fronk, M.; Lehmann, D.; Mahns, B.; Knupfer, M.; Zahn, D. R. T. (AIP Adv., 2013)

(untitled) - Zahn, D. R. T.; Gavrila, G. N.; Gorgoi, M. (Chem. Phys., 2006)

(untitled) - Hill, I. G.; Kahn, A.; Soos, Z. G.; Pascal, R. A., Jr (Chem. Phys. Lett., 2000)

(untitled) - Brumboiu, I. E.; Totani, R.; de Simone, M.; Coreno, M.; Grazioli, C.; Lozzi, L.; Herper, H. C.; Sanyal, B.; Eriksson, O.; Puglia, C.; Brena, B. (J. Phys. Chem. A, 2014)

(untitled) - Grobosch, M.; Mahns, B.; Loose, C.; Friedrich, R.; Schmidt, C.; Kortus, J.; Knupfer, M. (Chem. Phys. Lett., 2011)

(untitled) - Kraus, R.; Grobosch, M.; Knupfer, M. (Chem. Phys. Lett., 2009)

(untitled) - Rangger, G. M.; Hofmann, O. T.; Romaner, L.; Heimel, G.; Bröker, B.; Blum, R.-P.; Johnson, R. L.; Koch, N.; Zojer, E. (Phys. Rev. B, 2009)

Low-dimensional molecular metals - Toyota, N.; Müller, J.; Lang, M. (Springer Science & Business Media, 2007)

Organic conductors, superconductors and magnets: from synthesis to molecular electronics - Ouahab, L.; Yagubskii, E. (Springer Science & Business Media, 2004)

(untitled) - Walzer, K.; Maennig, B.; Pfeiffer, M.; Leo, K. (Chem. Rev., 2007)

(untitled) - Aziz, E. F.; Vollmer, A.; Eisebitt, S.; Eberhardt, W.; Pingel, P.; Neher, D.; Koch, N. (Adv. Mater., 2007)

(untitled) - Lüssem, B.; Riede, M.; Leo, K. (Phys. Status Solidi A, 2013)

(untitled) - Lüssem, B.; Tietze, M. L.; Kleemann, H.; Hoßbach, C.; Bartha, J. W.; Zakhidov, A.; Leo, K. (Nat. Commun., 2013)

(untitled) - Lindner, S.; Knupfer, M.; Friedrich, R.; Hahn, T.; Kortus, J. (Phys. Rev. Lett., 2012)

(untitled) - Krupskaya, Y.; Rückerl, F.; Knupfer, M.; Morpurgo, A. F. (Adv. Mater. Interfaces, 2016)

(untitled) - Rückerl, F.; Waas, D.; Büchner, B.; Knupfer, M. (J. Electron Spectrosc. Relat. Phenom., 2017)

(untitled) - Toader, M.; Gopakumar, T. G.; Shukrynau, P.; Hietschold, M. (J. Phys. Chem. C, 2010)

(untitled) - Pinto, H.; Jones, R.; Goss, J. P.; Briddon, P. R. (J. Phys.: Condens. Matter, 2009)

(untitled) - Méndez, H.; Heimel, G.; Winkler, S.; Frisch, J.; Opitz, A.; Sauer, K.; Wegner, B.; Oehzelt, M.; Röthel, C.; Duhm, S.; Többens, D.; Koch, N.; et al. (Nat. Commun., 2015)

Photoemission in Solids I: General Principles - Cardona, M.; Ley, L. (Springer, 1978)

Photoemission in Solids II: Case Studies - Ley, L.; Cardona, M. (Springer, 1979)

Photoelectron spectroscopy: principles and applications - Hüfner, S. (Springer Science & Business Media, 2013)

(untitled) - Smith, N. V. (Rep. Prog. Phys., 1988)

(untitled) - Himpsel, F.; Fauster, T. (J. Vac. Sci. Technol., A, 1984)

Unoccupied Electronic States - Fuggle, J. C.; Inglesfield, J. E. (Introduction, 1992)

(untitled) - Fink, J. (Adv. Electron. Electron Phys., 1989)

Unoccupied Electronic States - Fink, J. (Transmission electron energy-loss spectroscopy, 1992)

(untitled) - Roth, F.; König, A.; Fink, J.; Büchner, B.; Knupfer, M. (J. Electron Spectrosc. Relat. Phenom., 2014)

(untitled) - Knupfer, M.; Pichler, T.; Golden, M. S.; Fink, J.; Murgia, M.; Michel, R. H.; Zamboni, R.; Taliani, C. (Phys. Rev. Lett., 1999)

Handbook of Ellipsometry - Tompkins, H. G.; Irene, E. A. (William Andrew, 2005)

Spectroscopic Ellipsometry - Fujiwara, H. (Wiley, 2007)

Tailoring the Electronic and Optical Properties of Molecular Thin Films by Reducing and Oxidising Agents - Haidu, F. (Technische Universität Chemnitz, 2014)

NEXAFS Spectroscopy - Stöhr, J. (Springer, 1992)

(untitled) - Pederson, M. R.; Jackson, K. A. (Phys. Rev. B, 1990)

(untitled) - Pederson, M. R.; Porezag, D. V.; Kortus, J.; Patton, D. C. (Phys. Status Solidi B, 2000)

(untitled) - Porezag, D.; Pederson, M. R. (Phys. Rev. A, 1999)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Mahns, B.; Roth, F.; Grobosch, M.; Zahn, D. R. T.; Knupfer, M. (J. Chem. Phys., 2011)

(untitled) - Eastwood, D.; Edwards, L.; Gouterman, M.; Steinfeld, J. (J. Mol. Spectrosc., 1966)

Phthalocyanines: Properties and Applications - Leznoff, C. C.; Lever, A. B. P. (VCH Publishers, 1993)

(untitled) - Dini, D.; Hanack, M. (J. Porphyrins Phthalocyanines, 2004)

(untitled) - Lucia, E. A.; Verderame, F. D. (J. Chem. Phys., 1968)

(untitled) - Hernandez, J. P.; Choi, S.-i. (J. Chem. Phys., 1969)

(untitled) - Hollebone, B. R.; Stillman, M. J. (Chem. Phys. Lett., 1974)

(untitled) - Saito, T.; Sisk, W.; Kobayashi, T.; Suzuki, S.; Iwayanagi, T. (J. Phys. Chem., 1993)

(untitled) - Umeda, M.; Mohamedi, M.; Itoh, T.; Uchida, I. (J. Appl. Phys., 2001)

(untitled) - Auerhammer, J. M.; Knupfer, M.; Peisert, H.; Fink, J. (Surf. Sci., 2002)

(untitled) - Knupfer, M.; Schwieger, T.; Peisert, H.; Fink, J. (Phys. Rev. B, 2004)

(untitled) - Maslov, V. G. (Opt. Spectrosc., 2006)

(untitled) - Bondarev, I. V.; Popescu, A.; Younts, R. A.; Hoffman, B.; McAfee, T.; Dougherty, D. B.; Gundogdu, K.; Ade, H. W. (Appl. Phys. Lett., 2016)

(untitled) - Fielding, P. E.; MacKay, A. G. (Aust. J. Chem., 1975)

(untitled) - Williamson, B. E.; VanCott, T. C.; Boyle, M. E.; Misener, G. C.; Stillman, M. J.; Schatz, P. N. (J. Am. Chem. Soc., 1992)

(untitled) - Nyokong, T. (Struct. Bonding, 2010)

(untitled) - Stradi, D.; Díaz, C.; Martín, F.; Alcamí, M. (Theor. Chem. Acc., 2011)

(untitled) - Friedrich, R.; Hahn, T.; Kortus, J.; Fronk, M.; Haidu, F.; Salvan, G.; Zahn, D. R. T.; Schlesinger, M.; Mehring, M.; Roth, F.; Mahns, B.; Knupfer, M. (J. Chem. Phys., 2012)

(untitled) - Giovanelli, L.; Vilmercati, P.; Castellarin-Cudia, C.; Themlin, J.-M.; Porte, L.; Goldoni, A. (J. Chem. Phys., 2007)

(untitled) - Flatz, K.; Grobosch, M.; Knupfer, M. (J. Chem. Phys., 2007)

(untitled) - Roth, F.; König, A.; Kraus, R.; Knupfer, M. (J. Chem. Phys., 2008)

(untitled) - de Groot, F. M. F.; Fuggle, J. C.; Thole, B. T.; Sawatzky, G. A. (Phys. Rev. B, 1990)

(untitled) - Molodtsova, O. V.; Knupfer, M.; Aristov, V. Yu.; Vyalikh, D. V.; Zhilin, V. M.; Ossipyan, Yu. A. (J. Appl. Phys., 2008)

(untitled) - Aristov, V. Yu.; Molodtsova, O. V.; Maslyuk, V. V.; Vyalikh, D. V.; Bredow, T.; Mertig, I.; Preobrajenski, A. B.; Knupfer, M. (Org. Electron., 2010)

(untitled) - Nilson, K.; Åhlund, J.; Shariati, M.-N.; Schiessling, J.; Palmgren, P.; Brena, B.; Göthelid, E.; Hennies, F.; Huismans, Y.; Evangelista, F.; Rudolf, P.; Göthelid, M.; et al. (J. Chem. Phys., 2012)

(untitled) - Peisert, H.; Knupfer, M.; Fink, J. (Surf. Sci., 2002)

(untitled) - Grobosch, M.; Schmidt, C.; Kraus, R.; Knupfer, M. (Org. Electron., 2010)

(untitled) - Aristov, V. Yu.; Molodtsova, O. V.; Knupfer, M. (Org. Electron., 2011)

(untitled) - Marom, N.; Kronik, L. (Appl. Phys. A, 2009)

(untitled) - Giovannetti, G.; Brocks, G.; van den Brink, J. (Phys. Rev. B, 2008)

(untitled) - Wu, X.; Xu, C.; Wang, K.; Xiao, X. (J. Phys. Chem. C, 2016)

(untitled) - Phan, Q. T. N.; Heguri, S.; Tamura, H.; Nakano, T.; Nozue, Y.; Tanigaki, K. (Phys. Rev. B, 2016)

(untitled) - Ruff, A.; Sing, M.; Claessen, R.; Lee, H.; Tomić, M.; Jeschke, H. O.; Valentí, R. (Phys. Rev. Lett., 2013)

(untitled) - Caputo, M.; Di Santo, G.; Parisse, P.; Petaccia, L.; Floreano, L.; Verdini, A.; Panighel, M.; Struzzi, C.; Taleatu, B.; Lal, C.; Goldoni, A. (J. Phys. Chem. C, 2012)

(untitled) - Mahns, B.; Roth, F.; Knupfer, M. (J. Chem. Phys., 2012)

(untitled) - Knupfer, M.; Peisert, H.; Schwieger, T. (Phys. Rev. B, 2001)

(untitled) - Brühwiler, P. A.; Maxwell, A. J.; Nilsson, A.; Mårtensson, N.; Gunnarsson, O. (Phys. Rev. B, 1993)

(untitled) - Knupfer, M.; Poirier, D. M.; Weaver, J. H. (Phys. Rev. B, 1994)

(untitled) - Lof, R. W.; van Veenendaal, M. A.; Koopmans, B.; Jonkman, H. T.; Sawatzky, G. A. (Phys. Rev. Lett., 1992)

(untitled) - Hotta, S.; Kobayashi, H. (Synth. Met., 1994)

(untitled) - Sato, A.; Okada, M.; Saito, K.; Sorai, M. (Acta Crystallogr., Sect. C, 2001)

(untitled) - Zhu, L.; Yi, Y.; Li, Y.; Kim, E.-G.; Coropceanu, V.; Brédas, J.-L. (J. Am. Chem. Soc., 2012)

(untitled) - Mahns, B.; Kataeva, O.; Islamov, D.; Hampel, S.; Steckel, F.; Hess, C.; Knupfer, M.; Büchner, B.; Himcinschi, C.; Hahn, T.; Renger, R.; Kortus, J. (Cryst. Growth Des., 2014)

(untitled) - Yoshida, Y.; Kumagai, Y.; Mizuno, M.; Isomura, K.; Nakamura, Y.; Kishida, H.; Saito, G. (Cryst. Growth Des., 2015)

(untitled) - Kataeva, O.; Khrizanforov, M.; Budnikova, Y.; Islamov, D.; Burganov, T.; Vandyukov, A.; Lyssenko, K.; Mahns, B.; Nohr, M.; Hampel, S.; Knupfer, M. (Cryst. Growth Des., 2015)

(untitled) - Chernenkaya, A.; Morherr, A.; Backes, S.; Popp, W.; Witt, S.; Kozina, X.; Nepijko, S. A.; Bolte, M.; Medjanik, K.; Öhrwall, G.; Krellner, C.; Baumgarten, M.; et al. (J. Chem. Phys., 2016)

(untitled) - Morherr, A.; Witt, S.; Chernenkaya, A.; Bäcker, J.-P.; Schönhense, G.; Bolte, M.; Krellner, C. (Phys. B (Amsterdam, Neth.), 2016)

(untitled) - Hu, P.; Du, K.; Wei, F.; Jiang, H.; Kloc, C. (Cryst. Growth Des., 2016)

(untitled) - Rückerl, F.; Mahns, B.; Dodbiba, E.; Nikolis, V.; Herzig, M.; Büchner, B.; Knupfer, M.; Hahn, T.; Kortus, J. (J. Chem. Phys., 2016)

(untitled) - Poirier, D. M. (Appl. Phys. Lett., 1994)

(untitled) - Knupfer, M.; Poirier, D. M.; Weaver, J. H. (Phys. Rev. B, 1994)

(untitled) - Poirier, D. M.; Olson, C. G.; Weaver, J. H. (Phys. Rev. B, 1995)

(untitled) - Poirier, D. M.; Ownes, D. W.; Weaver, J. H. (Phys. Rev. B, 1995)

(untitled) - Andjelković, L.; Stepanović, S.; Vlahović, F.; Zlatar, M.; Gruden, M. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Nesbitt, H. W.; Banerjee, D. (Am. Mineral., 1998)

(untitled) - Kroll, T.; Kraus, R.; Schönfelder, R.; Aristov, V. Yu.; Molodtsova, O.; Hoffmann, P.; Knupfer, M. (J. Chem. Phys., 2012)

(untitled) - Oku, M.; Hirokawa, K.; Ikeda, S. (J. Electron Spectrosc. Relat. Phenom., 1975)

(untitled) - Mori-Sánchez, P.; Cohen, A. J.; Yang, W. (Phys. Rev. Lett., 2008)

(untitled) - Dixon, D. A.; Calabrese, J. C.; Miller, J. S. (J. Phys. Chem., 1989)

(untitled) - Müller, E.; Mahns, B.; Büchner, B.; Knupfer, M. (J. Chem. Phys., 2015)

(untitled) - Le, T. H.; Lu, J.; Bond, A. M.; Martin, L. L. (Inorg. Chim. Acta, 2013)

(untitled) - Lever, A. B. P.; Pickens, S. R.; Minor, P. C.; Licoccia, S.; Ramaswamy, B. S.; Magnell, K. (J. Am. Chem. Soc., 1981)

(untitled) - Clack, D. W.; Yandle, J. R. (Inorg. Chem., 1972)

(untitled) - Wang, J.; Wang, H.; Yan, X.; Huang, H.; Yan, D. (Appl. Phys. Lett., 2005)

(untitled) - Alves, H.; Molinari, A. S.; Xie, H.; Morpurgo, A. F. (Nat. Mater., 2008)

(untitled) - Nakano, M.; Alves, H.; Molinari, A. S.; Ono, S.; Minder, N.; Morpurgo, A. F. (Appl. Phys. Lett., 2010)

(untitled) - Lezama, I. G.; Nakano, M.; Minder, N. A.; Chen, Z.; Di Girolamo, F. V.; Facchetti, A.; Morpurgo, A. F. (Nat. Mater., 2012)

(untitled) - Alves, H.; Pinto, R. M.; Maçôas, E. S. (Nat. Commun., 2013)

(untitled) - Krupskaya, Y.; Lezama, I. G.; Morpurgo, A. F. (Adv. Funct. Mater., 2016)

(untitled) - Molodtsova, O. V.; Knupfer, M.; Ossipyan, Yu. A.; Aristov, V. Yu. (J. Appl. Phys., 2008)

(untitled) - Petraki, F.; Peisert, H.; Hoffmann, P.; Uihlein, J.; Knupfer, M.; Chassé, T. (J. Phys. Chem. C, 2012)

(untitled) - Lindner, S.; Mahns, B.; Treske, U.; Vilkov, O.; Haidu, F.; Fronk, M.; Zahn, D. R. T.; Knupfer, M. (J. Chem. Phys., 2014)

(untitled) - Åhlund, J.; Nilson, K.; Schiessling, J.; Kjeldgaard, L.; Berner, S.; Mårtensson, N.; Puglia, C.; Brena, B.; Nyberg, M.; Luo, Y. (J. Chem. Phys., 2006)

(untitled) - Shariati, M.-N.; Lüder, J.; Bidermane, I.; Ahmadi, S.; Göthelid, E.; Palmgren, P.; Sanyal, B.; Eriksson, O.; Piancastelli, M. N.; Brena, B.; Puglia, C. (J. Phys. Chem. C, 2013)

(untitled) - Kroll, T.; Aristov, V. Yu.; Molodtsova, O. V.; Ossipyan, Yu. A.; Vyalikh, D. V.; Büchner, B.; Knupfer, M. (J. Phys. Chem. A, 2009)

(untitled) - Petraki, F.; Peisert, H.; Biswas, I.; Aygül, U.; Latteyer, F.; Vollmer, A.; Chassé, T. (J. Phys. Chem. Lett., 2010)

(untitled) - Petraki, F.; Peisert, H.; Latteyer, F.; Aygül, U.; Vollmer, A.; Chassé, T. (J. Phys. Chem. C, 2011)

(untitled) - Bai, Y.; Buchner, F.; Kellner, I.; Schmid, M.; Vollnhals, F.; Steinrück, H.-P.; Marbach, H.; Gottfried, J. M. (New J. Phys., 2009)

(untitled) - Petraki, F.; Peisert, H.; Biswas, I.; Chassé, T. (J. Phys. Chem. C, 2010)

(untitled) - Lindner, S.; Treske, U.; Grobosch, M.; Knupfer, M. (Appl. Phys. A, 2011)

(untitled) - Lindner, S.; Treske, U.; Knupfer, M. (Appl. Surf. Sci., 2013)

(untitled) - Gottfried, J. M. (Surf. Sci. Rep., 2015)

(untitled) - Friedrich, R.; Lindner, S.; Hahn, T.; Loose, C.; Liebing, S.; Knupfer, M.; Kortus, J. (Phys. Rev. B, 2013)

(untitled) - Lindner, S.; Mahns, B.; König, A.; Roth, F.; Knupfer, M.; Friedrich, R.; Hahn, T.; Kortus, J. (J. Chem. Phys., 2013)